Remedies for financial crises in the classical and neoclassical literature - David Laidler (The University of Western Ontario, Department of Economics, 2000)
This paper traces the evolution of debate about the question of Rules versus Discretion in monetary policy from about 1800 until the mid 1930s. Particular attention is paid to long-versus-short-run issues, notably with respect to the 1844 Bank Charter Act, and the Bagehot Principle, as well as to the effects of developments in the theory of value, the cycle and index numbers on economists' perception on the scope of monetary policy. A brief discussion of post-World-War-2 developments links this material to present day concerns and common themes are noted.
Keywords: 330; Geldpolitik; Dogmengeschichte; Goldwährung; Klassische Theorie; Neoklassik; Theorie; Finanzmarktkrise